Nitrogen-enriched, ordered mesoporous carbons for potential electrochemical energy storage - Zhu, Jinhui; Yang, Jun; Miao, Rongrong; Yao, Zhaoquan; Zhuang, Xiaodong; Feng, Xinliang (Journal of Materials Chemistry A, 2016)
Nitrogen-doped (N-doped) porous carbons have drawn increasing attention due to their high activity for electrochemical catalysis, and high capacity for lithium-ion (Li-ion) batteries and supercapacitors. So far, the controlled synthesis of N-enriched ordered mesoporous carbons (N-OMCs) for Li-ion batteries is rarely reported due to the lack of a reliable nitrogen-doping protocol that maintains the ordered mesoporous structure. In order to realize this, in this work, ordered mesoporous carbons with controllable N contents were successfully prepared by using melamine, F127 and phenolic resin as the N-source, template and carbon-source respectively via a solvent-free ball-milling method. The as-prepared N-OMCs which showed a high N content up to 31.7 wt% were used as anodes for Li-ion batteries. Remarkably, the N-OMCs with an N content of 24.4 wt% exhibit the highest reversible capacity (506 mA h g-1) even after 300 cycles at 300 mA g-1 and a capacity retention of 103.3%. N-OMCs were also used as electrode materials in supercapacitors and a capacity of 150 F g-1 at 0.2 A g-1 with stable cycling up to 2500 times at 1 A g-1 was achieved. These attractive results encourage the design and synthesis of high heteroatom content ordered porous carbons for applications in the field of energy storage and conversion.
CRIS-Team Scopus Importer:2023-03-20